Angola 1992 "Hope in the Face of Anguish" - Weinberg, Paul (Kronos: Southern African Histories, 2019)
In 1980 I photographed P. W. Botha, then President of South Africa taking a salute during a military parade at the hallowed shrine of white supremacy, the Voortrekker Monument. It was a symbol of the times and went on to be used numerously by the alternate press and anti-apartheid movements within and outside the country. I was not on any assignment, but my own. Six years earlier, I had been conscripted as a young white South African at the age of seventeen years and two months into the South African Infantry. I spent my last three months of that year on the Namibian/ Angolan border. But I was lucky. I was fortunate to see no action, but at the same time, deeply aware of how us young conscriptees had been coerced to do the dirty work and be the cannon fodder for apartheid’s war in southern Africa, and integrally part of its war machine internally. A year later, 1975, with the demise of the Portuguese government, its control of its former colonies and the rise to power of the liberation forces within them, I would have been part of the invasion into Angola, an invasion that turned the tide on southern African politics. P. W. Botha, not long before he became President, initiated in 1979, as Minister of Defense, what he saw as the ‘Total Onslaught’.